Avaliação bioagronômica de pessegueiro (Prunus persica (L.) Batsch) submetido a diferentes porta-enxertos - Picolotto, Luciano (2009)
In Horticulture, differently from most annual crops, the use of rootstocks is a very common practice used among growers. So, the knowing of the scion/rootstock interaction on the scion is very important to the orchard management. This work aimed to evaluate the influence of rootstock on the vegetative, phenological, and productive development, and on fruit quality of peach tree (Prunus persica (L.) Batsch). Three peach cultivars were used: Chimarrita, Granada and Maciel. For each cultivar interaction it was evaluated trunk diameter, canopy volume, pruning weight, budburst time, flowering time, flower density, chlorophyll amount, leaf specific area, scaffold branches length, yield, fruit weight, fruit color, fruit flesh firmness, total soluble solid content (SST), titratable acidity (TA), SST/TA ratio, total phenols and ripening time. The results were: I) For the cv. Chimarrita, the rootstocks Capdeboscq , Okinawa and Tsukuba 1 showed better performance regarding trunk diameter, branches lengths, canopy volume, pruning weight, chlorophyll content. The largest number of flowers in the branches was only observed in trees raised on Capdeboscq . Red color was more intensity in fruits of trees grafted on GF 305 and red-yellow whether grafted on Okinawa . The fruit quality was altered by the rootstocks Capdeboscq , Tsukuba 1 and Okinawa , once higher TSS/TA ratio and color shade, lower flesh firmness and total phenols content were found. II) For cv. Granada, both air layering and seed propagations showed advantages and equal performances. Among rootstocks, it could not been possible to indicate the more adequate one, once each variable responded differently. However, important variables such as trunk diameter and scaffold branches length allowed better development of the cultivar scion when these were grafted on Okinawa and Capdeboscq . Also, Capdeboscq and Aldrigui provided redder fruits. Aldrigui and Okinawa influenced in larger fruit flesh. The studies with the rootstocks Capdeboscq , Okinawa and Aldrigui allowed to verify that canopy volume development, branch length and fruit ripening were not affected. III) For cv. Maciel, the variables were differently affected by the rootstocks. The larger tree vigor was verified by the rootstocks Indústria , Aldrighi , Nemaguard , Tsukuba 1 and Okinawa clone 1 , based on trunk diameter, canopy volume, scaffold branch length (except Okinawa clone 1 ) and pruning intensity (except for Industria ). The analysis also allowed to verify a higher content of chlorophyll with Nemaguard , Tsukuba 1 , Okinawa clone 1 , Rubira and Indústria . Leaf fall time was delayed in trees raised on Aldrigui . Fruit color and weight and yield showed inverse behaviors among rootstocks in the different crop seasons. Using Okinawa clone 1 as rootstocks, the fruits had higher fruit flesh firmness, lower TSS and TSS/TA ratio. It was possible to verify in the experiments that no rootstock effects on leaf fall and on the beginning of budburst, and also few makeable effects on flowering time. Based on the different results, the vegetative and phenological development and fruit quality of the cvs. Chimarrita, Granada and Maciel are affected by rootstocks.